Pengaruh Lingkungan, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan: (The Influence of Work Environment, Motivation and Work Discipline Toward Employee Performance) - Daspar Daspar (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2020)
This study aims to analyze the effect of work environment, motivation and discipline on the performance of PT. Astra Honda Motor. Research data from questionnaire and secondary data. The sampling method used was probability sampling. From a population of 70 people, 70 people become the sample. The method of analysis used in this study is multiple linear regression. The result showed that work environment and discipline has positive effect on the performance, while motivation has no effect on the performance.